2005
DOI: 10.1007/s00018-005-5373-z
|View full text |Cite
|
Sign up to set email alerts
|

Lactoferricin

Abstract: The peptide lactoferricin (Lfcin) can be released from the multifunctional protein lactoferrin (LF) through proteolysis by pepsin under acidic conditions, a reaction that occurs naturally in the stomach. Lfcin encompasses a large portion of the functional domain of the intact protein, and in many cases it not only retains the activities of LF but is more active. Lfcin possesses strong antimicrobial and weak antiviral activities, and it also has potent antitumor and immunological properties. This review covers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
196
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 447 publications
(202 citation statements)
references
References 67 publications
5
196
0
1
Order By: Relevance
“…Furthermore, it will be interesting to compare analogous peptides derived from lactoferrin of different species. In the past, the antimicrobial characteristics of bovine lactoferrin-derived peptides have been compared in detail with those of their human counterparts (13). Because of its human origin, the hLF peptide is expected to be non-immunogenic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it will be interesting to compare analogous peptides derived from lactoferrin of different species. In the past, the antimicrobial characteristics of bovine lactoferrin-derived peptides have been compared in detail with those of their human counterparts (13). Because of its human origin, the hLF peptide is expected to be non-immunogenic.…”
Section: Discussionmentioning
confidence: 99%
“…The hLF N-terminal domain in particular carries potent activity against pathogens (13). In the gastrointestinal tract this domain can be cleaved through pepsin digestion resulting in the release of an antimicrobial peptide called lactoferricin (14).…”
mentioning
confidence: 99%
“…The cationic domain of the N-terminal region of LF, lactoferricin, plays an important role in the direct bactericidal effects. 33,[36][37][38] Yoshinari et al reported that the modification of Ti surface with titaniumbinding peptides (minTBP-1) and lactoferricin showed a reduction in the bioactivity of P. gingivalis. 39 Although the antibacterial mechanism of LF on gram-positive pathogens is still not well understood, the interaction between LF and the cell membrane of gram-positive bacteria has been reported.…”
Section: B Inhibition Of S Gordonii Adhesion and The Bactericidal Ementioning
confidence: 99%
“…In general, AMPs are cationic, often amphipathic, which primarily kill bacteria by interacting and disrupting their cell membrane [10][11][12][13] . In a previous study, we introduced the 1-11 antimicrobial sequence of the human lactoferrin protein (hLf), the hLf1-11 peptide, as a potent AMP with capacity to reduce bacterial adhesion on titanium implants 8 .…”
Section: Introductionmentioning
confidence: 99%